2020
DOI: 10.21203/rs.2.15717/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Immune Classification for the PD-L1 Expression and Tumour-Infiltrating Lymphocytes in Colorectal Adenocarcinoma

Abstract: Background Colorectal adenocarcinoma is the third most common cancer worldwide and a leading cause of cancer-related death. The recent emergence of diverse immunotherapeutic agents has made it crucial to interpret a complex tumour microenvironment intermingled with tumour-infiltrating immune cells to predict the immunotherapeutic response rate. However, in colorectal adenocarcinoma, studies are lacking that provide detailed analyses of programmed death-ligand 1 (PD-L1) and tumour-infiltrating lymphocytes (TIL… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 29 publications
(28 reference statements)
1
8
0
Order By: Relevance
“…[6] To make matters more complex, mismatch repair (MMR) status may differentially impact PD-L1 expression related to survival. In this study, similar to the findings of Noh et al, [8] we found that a high density of PD-L1 expression correlated with hereditary non-polyposis colorectal cancer (HNPCC) patients and early tumor stage; however, the significance of PD-L1 expression in MMR-proficient and MMR-deficient patients is currently unclear. Droeser et al [13] have demonstrated that a high PD-L1 expression in MMR-proficient CRC is correlated with improved overall survival, while Dunne et al [17] have reported that PD-L1 expression is associated with a significantly better DFS in MMR-deficient patients.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…[6] To make matters more complex, mismatch repair (MMR) status may differentially impact PD-L1 expression related to survival. In this study, similar to the findings of Noh et al, [8] we found that a high density of PD-L1 expression correlated with hereditary non-polyposis colorectal cancer (HNPCC) patients and early tumor stage; however, the significance of PD-L1 expression in MMR-proficient and MMR-deficient patients is currently unclear. Droeser et al [13] have demonstrated that a high PD-L1 expression in MMR-proficient CRC is correlated with improved overall survival, while Dunne et al [17] have reported that PD-L1 expression is associated with a significantly better DFS in MMR-deficient patients.…”
Section: Discussionsupporting
confidence: 91%
“…[1][2][3] However, different subsets of TILs are associated with various specific functions, and a variety of these subsets can improve therapeutic outcomes for CRC patients. [4][5][6][7][8] In contrast, immune escape by cancer cells has been increasingly reported in recent years. Continuous exposure to tumor antigens results in the exhaustion of immune cells (ICs) and leads to poor clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…This contrasts with known strong immunogenic tumours such as skin melanoma, renal cell and bladder cancer or head and neck and lung SCC, where TMIT I characterizes 40–50% of cases [ 21 ]. On the other hand, ITAC is comparable to adenocarcinomas of other organs such as lung, colon and stomach, with reports of 12–14%, 19% and 23% TMIT I, respectively [ 21 , 28 , 37 , 38 ].…”
Section: Discussionmentioning
confidence: 83%
“…Colt et al have drawn a contrary conclusion that infiltration of CD8+ T cells into cancer islands was more significantly associated with the relapse-free survival than CD8+ T cell infiltration into either total tumor or stroma, while the result was not related to ICIs therapy [64]. In the stroma, CD8+TILs show a strong positive association with positive PD-L1 expression [65,66]. Low stromal CD8+ T cells infiltration was positively correlated to an increased incidence of angiolymphatic invasion [67].…”
Section: Discussionmentioning
confidence: 99%